Frequency and distribution of early tooth loss and endodontic treatment needs of permanent first molars in a Turkish pediatric population - Demirbuga, Sezer; Tuncay, Oznur; Cantekin, Kenan; Cayabatmaz, Muhammed; Dincer, Asiye Nur; Kilinc, Halil İbrahim; Sekerci, Ahmet Ercan (European Journal of Dentistry, 2013)
Objectives: The objective of this study is to evaluate the frequency and distribution of early tooth loss and endodontic treatment needs of permanent first molars in a Turkish pediatric population. Materials and Methods: A total of 7,895 panoramic radiographs taken for routine dental examination at the Department of Oral Maxillofacial Radiology between 2008 and 2012 years were investigated. Two independent specialists evaluated early tooth loss and endodontic treatment needs of permanent first molars using panoramic radiography and patient anamnesis forms. The teeth were classified according to the following data: (a) Missing teeth, (b) teeth requiring extraction, (c) endodontically treated teeth (ETT), (d) teeth requiring endodontic therapy. The data also classified according to four factors: Age group (6-12 and 13-16), gender (boy and girl), jaw (mandible and maxilla) and side (right and left). A Chi-square test was used for statistical analyses. Results: A total of 19,488 and 12,092 teeth were evaluated in the child group and adolescent group respectively. All data were higher in adolescents than children (p < 0.001). For gender factor, only ETT was higher in girls than it was in boys (p < 0.001). For the jaw factor, all data were higher (p < 0.001) in mandible than in the maxilla. For the side factor, no statistical difference existed between right and left. Conclusions: Early tooth loss and endodontic treatment needs of permanent first molars showed variability according to age groups and jaws. When the results were compared according to the side and gender factors, no statistical difference was found (p > 0.05) except with the data of ETT in gender groups.
Keywords: Age; endodontic; gender; tooth loss